Carotid replacement with Dacron graft in 292 patients. (December 2016) - Koncar, Igor; Ribac, Jelena Z; Ilic, Nikola S; Dragas, Marko; Mutavdzic, Perica; Tomic, Ivan Z; Ristanovic, Natasa; Kostic, Dusan; Davidovic, Lazar
Introduction: In case of highly atherosclerotic carotid process, carotid graft replacement might be a potential solution for successful procedure. Many studies evaluated the results of vein and polytetrafluorethilen (PTFE) graft usage at the carotid bifurcation, while the experience on the Dacron graft due to extensive atherosclerotic process is missing. The aim of our study was to evaluate 30-day and long-term results of the Dacron graft on carotid artery used in patients with extensive atherosclerotic disease. Material and methods: This retrospective study analysed early and long-term neurological outcome as well as Dacron graft patency in patients operated with carotid reconstruction. Early results were confirmed by follow-up clinical examination, whereas late results were assessed by follow-up clinical examination as well as duplex sonographic examination at least 1 year after the surgery. As for statistical methods we used descriptive analysis tests, Chi-square test, and logistic regression. Results: Carotid graft replacement was performed in 292 patients, before endarterectomy in 155 (53.09%), or after already attempted unsuccessful eversion endarterectomy in 137 (46.91%). Nineteen (6.5%) patients had a stroke due to ipsilateral and contralateral ischaemia or haemorrhagic in 17 (5.8%), 1 (0.3%) and 1 (0.3%) patients, respectively. Significantly higher rate of strokes occurred when the graft reconstruction was used after the failure of endarterectomy (8.5% vs. 3.5%, p  = 0.029). Stroke and death rate was 7.19%. Factors that increased risk of early stroke were the length of plaque in the internal carotid artery measured intraoperatively ( p  = 0.025) and the surgical tactic to perform graft reconstruction after attempted extensive endarterectomy ( p  = 0.029). Conclusion: Low number of patients with carotid stenosis has extensive atherosclerotic process longer than 4 cm that might jeopardise eversion endarterectomy. Carotid graft replacement with Dacron graft provide early results that are comparable with other conduits; however, in such patients reconstruction should be selected individually based on surgical experience and anatomical distribution of stenotic disease. Due to high risk of stroke, only symptomatic patients with such extensive atherosclerotic disease should be operated.